2021
DOI: 10.3390/life11030258
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tocilizumab on Inflammatory Markers in Patients Hospitalized with Serious Infections. Case Series and Review of Literature

Abstract: Background: The human anti-IL-6 receptor antibody tocilizumab (TCZ) has been approved for the treatment of rheumatoid arthritis (RA) and giant cell arteritis (GCA). It is observed that CRP levels drop quickly after starting TCZ treatment. This may lead to misinterpretation of laboratory results when accessing the patient with infectious disease while on TCZ. We conducted this study to report cases treated with tocilizumab who developed serious infections with special reference to levels of CRP and to review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Interestingly, it was also reported that withdrawal of hydrocortisone treatment results in an inflammatory rebound phenomenon in septic shock patients [14]. Like corticosteroids, tocilizumab treatment also reduced CRP levels in patients with rheumatoid arthritis and in those suffering from giant cell arteritis [15]. Also in COVID-19 patients, reduction in PCT and CRP levels was observed in patients treated with tocilizumab [16].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, it was also reported that withdrawal of hydrocortisone treatment results in an inflammatory rebound phenomenon in septic shock patients [14]. Like corticosteroids, tocilizumab treatment also reduced CRP levels in patients with rheumatoid arthritis and in those suffering from giant cell arteritis [15]. Also in COVID-19 patients, reduction in PCT and CRP levels was observed in patients treated with tocilizumab [16].…”
Section: Introductionmentioning
confidence: 91%
“…No differences in patient characteristics were observed between the secondary infection and nosecondary infection groups for the D−T−, D+T− and D+T+ groups (Table 2). In patients who developed a secondary infection, a positive culture was obtained on median [IQR] day 14 [11][12][13][14][15][16][17][18][19] following ICU admission, which was designated day 0 for the following analyses.…”
Section: Pct and Crp Levels In Patients Who Developed Secondary Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relapse was characterized by a return of clinical symptoms (costochrondral pain, loss of appetite) and increased activity on an F-18-FDG PET scan. CRP level was probably not elevated at this time due to the masking effect of tocilizumab ( 10 ). After an unsuccessful attempt with abatacept, we concluded that for this patient with steroid-dependent relapsing polychondritis with severe steroid toxicity there were no other treatment options left, except for alloHSCT.…”
Section: Case Descriptionmentioning
confidence: 99%
“…One consequence of tocilizumab-mediated inhibition of the IL-6 signalling pathway is that routinely measured CRP concentrations are decreased [6]. In inflammatory arthritides, tocilizumab doses are administered every 2-4 weeks, resulting in variable attenuation of CRP responses to bacterial infection [7][8][9]. In COVID-19, single doses of tocilizumab are used [4,5], making the extent and duration of IL-6 signalling suppression less defined [10].…”
Section: Introductionmentioning
confidence: 99%